2020
DOI: 10.7759/cureus.7712
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Physician Cell Phone Numbers by Patients in an Orthopaedic Surgery Practice

Abstract: Introduction Orthopaedic surgeons choose to manage communication with their patients outside of official visits and interactions in a variety of ways, with some choosing to provide their personal cell phone number in order to provide patients with direct accessibility. The objective of this prospective study is to explore to what extent patients utilize the cell phone numbers of orthopaedic surgeons in the immediate period after it is provided to them. Methods Seven fellowship-trained orthopaedic surgeons from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This low incidence of PPN utilization is consistent with data previously published in the literature. Rogero et al 1 conducted a similar study of orthopedic surgery patients and found that 10.1% of patients who received their provider’s personal phone number called their surgeon in a 30-day timeframe, with 45.2% of calls considered inappropriate (vs 18.2% in our study). Survey results published by Chin et al 2 found that 85% of respondents (201 completed surveys) who had not received their provider’s personal phone number would consider using it to contact their surgeon if it was provided.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This low incidence of PPN utilization is consistent with data previously published in the literature. Rogero et al 1 conducted a similar study of orthopedic surgery patients and found that 10.1% of patients who received their provider’s personal phone number called their surgeon in a 30-day timeframe, with 45.2% of calls considered inappropriate (vs 18.2% in our study). Survey results published by Chin et al 2 found that 85% of respondents (201 completed surveys) who had not received their provider’s personal phone number would consider using it to contact their surgeon if it was provided.…”
Section: Discussionsupporting
confidence: 52%
“…The risks associated with this practice would be further reduced with the accurate identification of patients likely to abuse a provider's PPN. 1,4 This study found that only 10% of participants suspected to abuse their provider's PPN were accurately identified. In addition, 10 out of 266 participants randomized to receive their provider's PPN were suspected to abuse it, representing a small rate of 3.8%.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations